Development of Web-Based Computer-Tailored Advice to Promote Physical Activity Among People Older Than 50 Years - Peels, Denise A; van Stralen, Maartje M; Bolman, Catherine; Golsteijn, Rianne HJ; de Vries, Hein; Mudde, Aart N; Lechner, Lilian (JMIR Publications, 2012)
BackgroundThe Active Plus project is a systematically developed theory- and evidence-based, computer-tailored intervention, which was found to be effective in changing physical activity behavior in people aged over 50 years. The process and effect outcomes of the first version of the Active Plus project were translated into an adapted intervention using the RE-AIM framework. The RE-AIM model is often used to evaluate the potential public health impact of an intervention and distinguishes five dimensions: reach, effectiveness, adoption, implementation, and maintenance. ObjectiveTo gain insight into the systematic translation of the first print-delivered version of the Active Plus project into an adapted (Web-based) follow-up project. The focus of this study was on the reach and effectiveness dimensions, since these dimensions are most influenced by the results from the original Active Plus project. MethodsWe optimized the potential reach and effect of the interventions by extending the delivery mode of the print-delivered intervention into an additional Web-based intervention. The interventions were adapted based on results of the process evaluation, analyses of effects within subgroups, and evaluation of the working mechanisms of the original intervention. We pretested the new intervention materials and the Web-based versions of the interventions. Subsequently, the new intervention conditions were implemented in a clustered randomized controlled trial. ResultsAdaptations resulted in four improved tailoring interventions: (1) a basic print-delivered intervention, (2) a basic Web-based intervention, (3) a print-delivered intervention with an additional environmental component, and (4) a Web-based version with an additional environmental component. Pretest results with participants showed that all new intervention materials had modest usability and relatively high appreciation, and that filling in an online questionnaire and performing the online tasks was not problematic. We used the pretest results to improve the usability of the different interventions. Implementation of the new interventions in a clustered randomized controlled trial showed that the print-delivered interventions had a higher response rate than the Web-based interventions. Participants of both low and high socioeconomic status were reached by both print-delivered and Web-based interventions. ConclusionsTranslation of the (process) evaluation of an effective intervention into an adapted intervention is challenging and rarely reported. We discuss several major lessons learned from our experience. Trial RegistrationNederlands Trial Register (NTR): 2297; http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=2297 (Archived by WebCite at http://www.webcitation.org/65TkwoESp).